A Child with Crohn's Disease: Problems and Stress Level of Parents-Caregivers-A Cross-Sectional Study - Małgorzata Pasek; Monika Stoietskyi; Anna Goździalska; Małgorzata Jochymek (MDPI AG, 2024)
Crohn's disease (CD) is a chronic inflammatory bowel disease. The perception of the disease, its troublesome symptoms and the highly involved treatment mean that living with CD requires not only the affected child having to learn to cope with it, but also their parents. The aim of the study was to examine the problems and levels of stress in parents-caregivers of children with CD. The study was cross-sectional and conducted using the diagnostic survey method. An original questionnaire was used to assess the socio-demographic situation and problems of caring for a child with CD, and the standardised PSS-10 questionnaire was added. The study group consisted of 60 parents who accompanied their children during hospitalization. The surveyed caregivers of children with CD found it difficult to maintain a specialised diet and deal with the need for hospitalization and the chronic use of medications. Access to the necessary knowledge about the disease posed the least difficulty in everyday life for a child with CD. The vast majority of parents (50, 83.34%) felt a high level of stress related to caring for a child with CD and, simultaneously, a lack of acceptance of the child's disease (39, 65%). The age of the respondents did not have a statistically significant effect on the occurrence of problems related to everyday functioning. The acceptance of the child's disease by the parents and informal caregivers of children with CD reduced their stress level. Parents could count on support from their relatives but, unfortunately, institutional support was not properly provided.